PENGARUH HARGA TRANSFER DAN INTENSITAS MODAL TERHADAP PENGHINDARAN PAJAK - Leiliy Nur Aryani; Rianto - (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
This study aims to determine the effect of Transfer Pricing and Capital Intensity on Tax Avoidance. The sample used in this study is a company listed on the Indonesia Stock Exchange (IDX) and publishes a complete financial report in 2018-2022 with 10 sample companies using purposive sampling method. The independent variable of this study is the transfer pricing measured by the related parties accounts receivable of the total account receivable and capital intensity measured by the total fixed assets of the total assets. The dependent variable of this study is the Tax Avoidance which is measured by ETR of the profit before tax. The results show that Transfer Pricing has a positif significant effect on Tax Avoidance and Capital Intensiry has positif significant on Tax Avoidance.